Legacies of the sublime : literature, aesthetics, and freedom from Kant to Joyce - Kitson, Christopher, 1987- (SUNY series, studies in the long nineteenth century., 2019)
Legacies of the Sublime' offers a highly original, subtle and persuasive account of the aesthetics of the sublime in late nineteenth- and early twentieth-century literature, philosophy, and science. Christopher Kitson reveals the neglected history of how Kant?s theory of the sublime in the 'Critique of Judgment' cast a shadow over the next century and more of literature and thought. In each chapter, close readings weave together literary works with philosophical and scientific ones in order to clarify the complex dialogues between them. Through these readings, Kitson shows how the sublime survived well after the heyday of romanticism as a way of representing human freedom. This new context produces fresh interpretations of canonical literary works, by Thomas Carlyle, H.G. Wells, Joseph Conrad, and James Joyce, with reference to important theoretical texts by Karl Marx and Friedrich Engels, Arthur Schopenhauer, Friedrich Nietzsche, and Sigmund Freud. Kitson follows the sublime?s various manifestations and mutations, through the nineteenth century?s industrial grandeur and the vertiginous prospects of deep time, into the early twentieth century?s darkly ironic and uncanny versions. A welcome contribution to the study of the long nineteenth century, this work reveals an unexamined chapter in intellectual history and in the story of the modern self.